PENGARUH LITERASI KEUANGAN, KONTROL DIRI DAN TEMAN SEBAYA TERHADAP SAVING BEHAVIOR PADA ANAK SEKOLAH MENENGAH ATAS NEGRI 10 TASIKMALAYA - Violita Renata Nurseptia; Astri Srigustini; Edi Fitriana Afriza (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem in research is that saving behavior in school children is still low. The aim of this research is to determine